Some factors related to U.P. High School senior students' career preferences - Cervantes, Gregoria L. 1928- (s.n.], 1973)
This paper identified certain factors related to senior high school students' career preferences. It also tried to relate career preferences with factors such as mental ability, academic achievement, parents' profession or occupation and socio economic status of the family.